2011
DOI: 10.2478/v10125-011-0005-8
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the invasive slug species <i>Arion lusitanicus</i> Mabille, 1868 (Gastropoda: Pulmonata: Stylommatophora) and dangers to garden crops - a literature review with some new data

Abstract: The distribution of Arion lusitanicus Mabille and the damage caused by the slug were studied in 1993-2009. A total of 38 sites were examined, characterised in terms of location, time of appearance and density of the slug, type and size of crops affected, and degree of damage to plants. At the start of the 1990s A. lusitanicus occurred only around Rzeszów and in the Sub-Carpathian region. In 1997 it started to appear in other regions of Poland. The rate of its spread was found to have increased significantly, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…obs.). The same pattern has also been found in other countries (Kozlowski & Kozlowski 2011). However, it seems to have established populations in a few deciduous forests in Sweden (von Proschwitz, T., pers.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…obs.). The same pattern has also been found in other countries (Kozlowski & Kozlowski 2011). However, it seems to have established populations in a few deciduous forests in Sweden (von Proschwitz, T., pers.…”
Section: Discussionsupporting
confidence: 71%
“…The invasive slug Arion vulgaris (Moquin-Tandon, 1855) (in most of the literature up to now referred to as A. lusitanicus 18�8 (Anderson 2005;Quinteiro et al 2005)) has spread to many parts of Europe, including Scandinavia, during the last few decades (Reischütz 1984;Davies 1987;von Proschwitz 1992;Kaiser et al 1993;Dolmen & Winge 1997;Kozlowski and Kozlowski …”
mentioning
confidence: 99%
“…Slug densities of 100 slugs/m 2 were recorded from typical gathering sites with fresh plant debris, compost, deep ditches and shaded slopes of watercourses. In another study from Poland, an average number of 16.8 slugs/m 2 were observed in July in a clover cultivation (Kozlowski and Kozlowski, 2011).…”
Section: Level Of Slug Contaminationmentioning
confidence: 97%
“…One of these is the invasive slug Arion lusitanicus Mabille, 1868(A. vulgaris Moquin Tandom, 1885) (Anderson, 2005), which originates from the south-western part of Europe. Year by year, in Poland and all over Europe, significant crop damage is being caused by slugs Arion lusitanicus (Kozłowski, 2012;Kozłowski and Kozłowska, 2009;Kozłowski and Kozłowski, 2011). Observations have shown that the losses to crops caused by this slug are large, sometimes as high as 70%.…”
Section: Introductionmentioning
confidence: 99%